Analisis Metode dan Jenis Keputusan Dalam Literatur Sistematis Pengembangan Sistem Pendukung Keputusan - Steven, Wendy; Ayu, Tri Buana; Ariza, Agung Riski; Farisi, Ahmad (Universitas Multi Data Palembang, 2025)
This study examines the development of Decision Support Systems (DSS) in the last three years based on methods, types of decisions, software development, and their focus areas. General analysis shows that the DSS methods used include multicriteria analysis, machine learning, algorithm optimization, and fuzzy logic to support complex and data-driven decision making. DSS is applied in strategic, tactical, and operational decisions. In terms of software development, Agile and prototyping methods are dominant due to their complexity. The main areas of DSS application include business management, health, education, transportation, and the environment, with the aim of providing efficient and adaptive solutions. The results of this study describe the trends and applications of DSS and serve as references for research and implementation in various sectors.